Analysis Of The Community Satisfaction Index Regarding Public Services At The Pardasuka Village Office, Maje District, Kaur Regency - Herlina, Yeni; Akbar , Kaisar; Irwanto , Tito (Multidisciplinary Journals, 2025)
The Public Satisfaction Index (PSI) is an evaluation instrument used to measure the level of public satisfaction with the quality of public services. This assessment is conducted by comparing public expectations with the actual services received. The purpose of this study was to analyze the Public Satisfaction Index (PSI) regarding public services at the Pardasuka Village Office, Maje District, Kaur Regency. The method used was quantitative research with a descriptive approach, utilizing a survey as the data collection technique. The sample consisted of 150 respondents selected using accidental sampling. Data were analyzed using the Public Satisfaction Index (PSI) method in accordance with Regulation of the Minister of Administrative and Bureaucratic Reform Number 14 of 2017. The results showed that the PSI score for public services in Pardasuka Village, Maje District, Kaur Regency was 77.69, which falls into the Good category (service quality B). Of the nine assessment elements, implementer behavior and complaint handling received the highest scores, while completion time and implementer competence were elements that still needed improvement. Overall, the public is satisfied with the services provided, but it is suggested that improvements be made, particularly in terms of time efficiency and increasing the competence of officers so that the quality of service can continue to be improved.